The Role of AIRE in the Immunity Against Candida Albicans in a Model of Human Macrophages - Albuquerque, Jose Antonio Tavares de; Banerjee, Pinaki Prosad; Castoldi, Angela; Ma, Royce; Zurro, Nuria Bengala; Ynoue, Leandro Hideki; Arslanian, Christina; Barbosa-Carvalho, Marina Uchoa Wall; Correia-Deur, Joya Emilie de Menezes; Weiler, Fernanda Guimarães; Dias-da-Silva, Magnus Regios; Lazaretti-Castro, Marise; et al. (Frontiers in Immunology, 2018)
Autoimmune-polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a primary immunodeficiency caused by mutations in the autoimmune regulator gene (AIRE). Patients with AIRE mutations are susceptible to Candida albicans infection and present with autoimmune disorders. We previously demonstrated that cytoplasmic AIRE regulates the Syk-dependent Dectin-1 pathway. In this study, we further evaluated direct contact with fungal elements, synapse formation, and the response of macrophage-like THP-1 cells to C. albicans hyphae to determine the role of AIRE upon Dectin receptors function and signaling. We examined the fungal synapse (FS) formation in wild-type and AIRE-knockdown THP-1 cells differentiated to macrophages, as well as monocyte-derived macrophages from APECED patients. We evaluated Dectin-2 receptor signaling, phagocytosis, and cytokine secretion upon hyphal stimulation. AIRE co-localized with Dectin-2 and Syk at the FS upon hyphal stimulation of macrophage-like THP-1 cells. AIRE-knockdown macrophage-like THP-1 cells exhibited less Dectin-1 and Dectin-2 receptors accumulation, decreased signaling pathway activity at the FS, lower C. albicans phagocytosis, and less lysosome formation. Furthermore, IL-1β, IL-6, or TNF-α secretion by AIRE-knockdown macrophage-like THP-1 cells and AIRE-deficient patient macrophages were decreased compared to control cells. Our results suggest that AIRE modulates the FS formation and hyphal recognition, and help to orchestrate an effective immune response against C. albicans.